1996
DOI: 10.1590/s0074-02761996000600027
|View full text |Cite
|
Sign up to set email alerts
|

Temperature requirements of Chrysomya albiceps (Wiedemann, 1819) (Diptera, Calliphoridae) under laboratory conditions

Abstract: Chrysomya albiceps specimens were obtained from colonies established with larvae and adults collected at the Federal Rural University in Rio de Janeiro, Seropédica, State of Rio de Janeiro. The larval stage of C. albiceps was allowed to develop in climatic chambers at temperatures of 18, 22, 27 and 32 o C, and the pupal stage was allowed to develop at 22, 27 and 32 o C (60 ± 10% RH and 14 hr photoperiod).The duration and viability of the larval stage of C. albiceps at 18, 22, 27 and 32 o C were 21.30, 10.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 8 publications
5
24
0
1
Order By: Relevance
“…In this study, as other researches (Al-Shareef & AlQurashi, 2016;Grassberger et al, 2003;Queiroz, 1996;Grassberger & Reiter, 2001;Augul, 2009) we found that as the temperature increases, the length of the development is shortened. In C.albiceps, the length of larvae stage (first larval to Pupal instar) in 25°C and 30°C were 6 and 4 days, Queiroz (Queiroz, 1996) (5 days at 27°C); Augul and Jassim (Augul, 2009) (3 days at 30°C); AL-Shareef and AlQurashi(Al-Shareef & Al-Qurashi, 2016) (5 days); Richard et al (Richards et al, 2008) (5.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In this study, as other researches (Al-Shareef & AlQurashi, 2016;Grassberger et al, 2003;Queiroz, 1996;Grassberger & Reiter, 2001;Augul, 2009) we found that as the temperature increases, the length of the development is shortened. In C.albiceps, the length of larvae stage (first larval to Pupal instar) in 25°C and 30°C were 6 and 4 days, Queiroz (Queiroz, 1996) (5 days at 27°C); Augul and Jassim (Augul, 2009) (3 days at 30°C); AL-Shareef and AlQurashi(Al-Shareef & Al-Qurashi, 2016) (5 days); Richard et al (Richards et al, 2008) (5.…”
Section: Discussionsupporting
confidence: 84%
“…In C.albiceps, the length of larvae stage (first larval to Pupal instar) in 25°C and 30°C were 6 and 4 days, Queiroz (Queiroz, 1996) (5 days at 27°C); Augul and Jassim (Augul, 2009) (3 days at 30°C); AL-Shareef and AlQurashi(Al-Shareef & Al-Qurashi, 2016) (5 days); Richard et al (Richards et al, 2008) (5. 5 days); Shiravi et al (Shiravi et al, 2011) (2-3 days at 28°C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the others, data refer to the estimations obtained for the development of immatures in constant temperatures, which are in disagreement with results observed in this work (Wells & Kurahashi 1994;Aguiar-Coelho & Milward-de-Azevedo 1995;D'Almeida & Mello 1995;Queiroz & Milward-de-Azevedo 1996;Milwardde-Azevedo et al 1996;Paes et al 1997;Marchenko 2001;Mascarini & Prado 2002;Gabre et al 2005;Krüger et al 2008) (Table I). With the exception of estimates for S. crassipalpis, S. chlorogaster and H. segmentaria (Bonatto 1996;Krüger et al 2003;Thyssen 2005), which are close to the data obtained in ambient temperature, the remainder of the species presents a development period larger than what would be expected from ambient temperatures.…”
Section: Discussionsupporting
confidence: 47%